2000
DOI: 10.2466/pms.2000.91.3f.1027
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences on a Computerized Mental Rotation Task Disappear with Computer Familiarization

Abstract: The area of cognitive research that has produced the most consistent sex differences is spatial ability. Particularly, men consistently perform better on mental rotation tasks than do women. This study examined the effects of familiarization with a computer on performance of a computerized two-dimensional mental rotation task. Two groups of college students (N=44) performed the rotation task, with one group performing a color-matching task that allowed them to be familiarized with the computer prior to the rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…Interestingly, we have seen no evidence of gender differences in either the quantitative or qualitative assessments despite the longstanding assumption regarding individual differences in visualization and science achievement. This is not surprising since the construction project provides lengthy training and prior studies (Roberts & Bell, 2000;Scali, Brownlow, & Hicks, 2000) have shown that gender differences in spatial ability are largely due to experience and that training can eliminate gender bias. Our project facilitates long-term experience because it extends beyond a unit or lesson as a self-paced, out-of-class assignment.…”
Section: Figure 8 Stereo Kinemage Of the Active Site Of Ricin Showinmentioning
confidence: 94%
“…Interestingly, we have seen no evidence of gender differences in either the quantitative or qualitative assessments despite the longstanding assumption regarding individual differences in visualization and science achievement. This is not surprising since the construction project provides lengthy training and prior studies (Roberts & Bell, 2000;Scali, Brownlow, & Hicks, 2000) have shown that gender differences in spatial ability are largely due to experience and that training can eliminate gender bias. Our project facilitates long-term experience because it extends beyond a unit or lesson as a self-paced, out-of-class assignment.…”
Section: Figure 8 Stereo Kinemage Of the Active Site Of Ricin Showinmentioning
confidence: 94%
“…spatially relevant experience not assessed on the task itself) enhance spatial performance (see meta-analyses by Baenninger & Newcombe, 1989Marulis, Liu, Warren, Uttal, & Newcombe, 2007). Practice effects on spatial tests are often substantial, and in fact, long-term practice or repeated testing can sometimes lead to massive improvement and the obliteration of pre-existing differences among groups, for for women than men (Okagaki & Frensch, 1994;Subrahmayam & Greenfield, 1996), or even the elimination of gender differences (Kass et al, 1998;Lizarraga & Ganuza, 2003;Paramswaran, 1994;Paramswaran & De Lisi, 1996;Roberts & Bell, 2000), a recent metaanalysis still does not show differential effects of practice, or repeated testing, and training on men versus women (Marulis et al, 2007).…”
mentioning
confidence: 99%
“…), qui laissent moins de placeà la manipulation des informations visuospatiales (Baenninger & Newcombe, 1989 ;Brosnan, 1998). Alington et al (1992), Kass et al (1998) et Roberts & Bell (2000 ont néanmoins avancé que cette différence pouvaitêtre réduite après un entrainement spécifique des capacités visuo-spatiales et une familiarisation au travail informatique. Récemment, Wiedenbauer & JansenOsmann (2008) ont montré que l'entraînement des enfantsà la rotation manuelle d'un stimulus améliorait leur capacité de RM tout enéliminant les différences liées au genre.…”
Section: Effets Du Sexe Et De L'expérienceunclassified
“…On s'est egalement interrogé sur l'évolution des capacités individuelles de RMà la suite d'un entraînement (Alington et al, 1992 ;Kass et al, 1998 ;Roberts & Bell, 2000 ;Hoyek et al, 2009) (Rochford, 1985 ;Garg et al, 2001 ;Hegarty et al, 2008 ;Wanzel et al, 2007 ;Guillot et al, 2007a ;Hoyek et al, 2009). Pour cela, d'autres formes de tests de RM ontété utilisées, impliquant des lettres et des chiffres (Vingerhoets et al, 2001) et même des segments corporels (Parsons, 1994).…”
Section: Introductionunclassified